Reaching Hispanics with messages to prevent alcohol and other drug abuse. - Johnson, E M (1989)
Hispanics are often labeled a "hard-to-reach" population in the context of health communications, yet there are indicators that corporate interests increasingly are reporting successes in designing advertising and promotional campaigns targeting Hispanic markets. The authors suggest research priorities designed to promote more effective communications programming in the substance abuse field, and they identify three key target audiences: children and adolescents, women of childbearing age, and heavy-drinking men. The significance of the diversity within the Hispanic community; the opportunities to reinforce attitudes, norms, and behaviors that counter substance use; and the centrality of family are discussed as approaches to communications planning and message development.